Simulasi dan Pemetaan Banjir 1D dan 2D di Wilayah Hilir Sub-Das Lambidaro Menggunakan HEC-RAS - Ade Tricia Miranda; Hartini Hartini; Adji Sutama; Marice Agustini (Universitas Batanghari Jambi, 2026)
Flooding is one of the most destructive natural disasters and frequently occurs in densely populated residential areas located in lowland regions. Lowland areas with high population density generally have low infiltration capacity and high surface runoff, causing flooding to occur repeatedly during rainfall events. Palembang City is predominantly situated in lowland areas and has a relatively high population density. The downstream area of the Lambidaro sub-watershed is one of the densely populated lowland regions in Palembang City, making it highly vulnerable to flooding during rainfall events with certain intensities. This study aims to simulate and map flooding in the downstream area of the Lambidaro sub-watershed using the HEC-RAS program, in which flood discharge was first analyzed using the Nakayasu Synthetic Unit Hydrograph (HSS) method. Based on the flood analysis using the Nakayasu Synthetic Unit Hydrograph (HSS) method, a simulated peak flood discharge of 57.17 m³/s was obtained from the maximum effective rainfall during the observation period from January 1, 2026 to April 9, 2026, with an effective rainfall value of 43.376 mm. In this study, rainfall data were obtained from NASA POWER Data Access Viewer (DAV) satellite data, which were utilized as satellite-based rainfall estimation data for daily hydrological analysis while considering the limitations of the data and the need for verification using local observational records. Based on the 1D and 2D simulations using the HEC-RAS program, flooding in the downstream area of the Lambidaro sub-watershed was predominantly concentrated in areas surrounding the Lambidaro River, with floodwater depths reaching up to 0.73 meters.